Penggunaan Tentara Anak Oleh Aktor Selain Negara Ditinjau Dari Hukum Humaniter Internasional - Rahadian Diffaul Barraq Suwartono (Fakultas Hukum Universitas Islam Indonesia, 2020)
The use of children as combatants is not only carried out by the state, but also by actors other than the state. Children aged 8 to 14 are armed, trained and fielded in combats. The recruitment of child soldiers is generally prohibited by international law. There are several international legal instruments that prohibit the involvement of child soldiers in armed conflict. However, so far international legal arrangements have emphasized obligations on state subjects. This results in unclear regulations and legal accountability for the use of child soldiers by non-state actors. This research answers two problem formulations, First, how is the practice of using child soldiers by non-state actors?; Second, what is the concept of the responsibility of non-state actors for the crime of using child soldiers in international humanitarian law? This research is a normative study, using a statutory, historical, and conceptual approach. The results of this study concluded: First, the practice of using child soldiers in the field by non-state actors was carried out by recruiting their child soldiers forcibly and voluntarily, treating them very inhumanely, and assigning various kinds of child soldiers on their side based on age and sex; Second, the responsibility for a person who commits crimes using child soldiers can be in the form of individual responsibility or command responsibility.